Highly efficient synthesis of globular (bola)amphiphilic [5:1]hexakisadducts of C60 - Hörmann, Frank; Brettreich, Michael; Donaubauer, Wolfgang; Hampel, Frank; Hirsch, Andreas (Chemistry - A European Journal, 2013)
We report on the very facile access of a new family of amphiphilic and bola-amphiphilic fullerene [5:1]hexakisadducts 9 a-f and 11 a-e. The key point for this successful approach is the use of C-symmetrical fullerene pentakisadduct precursors 2 b-f allowing for the completely regioselective addition of a sixth malonate addend to complete the octahedral [5:1] addition pattern. For the synthesis of the new amphiphiles we first developed a new second-generation dendrimer containing 9 tert-butoxycarbonyl (Boc)-protected amino functions at the periphery and two new malonates containing 6 or 18 Boc-protected amino termini, respectively. The hexakisadducts contain up to 18 positive or negative charges at the dendritic moiety and either no or ten positive or negative charges at the unbranched malonate positions after deprotection with trifluoroacetic acid (TFA). The charge state at the termini is pH-dependent. Complete structural characterization of the new compounds was carried out by ESI mass spectrometry and by UV/Vis, FTIR, H NMR and C NMR spectroscopy. We were also able to obtain the first X-ray crystal structure of pentakisadduct (2 a) with a C-symmetrical addition pattern. The new amphiphilic hexakisadducts show interesting solubility properties in water. Initial investigations on the aggregation properties of the amphiphilic hexakisadduct 12 c by using dynamic light scattering (DLS) and conductivity measurements, show aggregates with a radius up to 200 nm and a critical micelle concentration (CMC) of approximately 8 mg L. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.